To Know Nothing: Apophatic Theology in the Dionysian Corpus - Todorovska, Marija (Živa Antika & The Faculty of Philosophy, Skopje, 2016)
The article briefly shows the major points of apophaticism in Pseudo-Dionysius, focusing on his stances of the incomprehensibility of God (the One, the Supreme Cause of everything, Being itself) and the limitations to men’s abilities of attaining any proper knowledge about his immeasurable greatness and infinite power. In an attempt at a brief overview of some of the aspects of his apophatic theology, chosen passages from the treatises The Divine Names, The Celestial Hierarchy and the Mystical Theology (as well as from two of his Letters) show his insistence on the ineffability and the incomprehensibility of God, the knowledge of him as limited to an experience of his manifestation in the world, and the non-knowledge achieved through denial of everything of this world including oneself, and the understanding that nothing can be affirmed or denied of God.